Understanding, collecting, and presenting data in New Englishes research: insights from ethnographic fieldwork in an Old Order Mennonite community - Neuhausen, Miriam (New englishes, new methods, 2023)
Against the background of my fieldwork in an isolated Old Order Mennonite community averse to secular norms and values, I suggest ethnographic fieldwork is key to understanding, collecting, and presenting New Englishes data. Before entering the field, researchers must begin to question principles that work in Western urban societies but may play out differently in lesser-studied communities. An understanding of the sociolinguistic realities in the community under investigation paves the way for the discovery of new social variables, access to speakers, and the accomplishment of meaningful research. I illustrate these benefits mainly in reference to the Labovian sociolinguistic interview. Finally, the paper argues that researchers need to ensure that their representation of the community is in line with the community’s interests.